Persona Branding in Building Customer-Based Brand Equity (CBBE) at Gibly Themed Cafe Giyanti Coffee Roastery Menteng - Yulianti; Anik Yuniati (International Journal of Travel, Hospitality and Events, 2025)
Objective: This study aims to analyze the role of branding personas in building brand experience and consumer loyalty at the Giyanti thematic cafe that carries the concept of the Studio Ghibli anime world in the midst of intense competition in the cafe business and changes in consumer behavior that increasingly prioritize emotional experiences, it is important for businesses to understand how branding elements can shape customer perceptions and attachments. Research Method: descriptive qualitative approach with direct observation method, social media observation, and SWOT analysis based on Customer-Based Brand Equity (CBBE) theory which includes four dimensions: brand awareness, brand meaning, brand response, and brand resonance. Results and Discussion: The results showed that although Giyanti Cafe succeeded in creating an imaginative and visually appealing thematic atmosphere, there were still weaknesses in building strong awareness, consistent service response, and active community involvement. Brand meaning is formed through nostalgic ambience and atmospheric differentiation, but has not been followed by a sustainable marketing strategy and customer loyalty. This research recommends strengthening storytelling, community collaboration, and a more consistent content and service strategy as important steps in increasing brand resonance and creating loyal customers. Implication: Based on the analysis of CBBE dimensions, Kafe Giyanti can improve the effectiveness of its brand persona by: a). Strengthening scheduled digital campaigns and consistent storytelling to build awareness and meaning. b). Improving customer service quality through staff training and monitoring operational standards. c). Creating loyalty programs and active communities to strengthen brand resonance. d). Establishing collaborations with thematic communities, such as anime, vintage, or local creator communities, so that the brand has an influential social network. Thus, Kafe Giyanti is not only present as a momentary thematic cafe, but as a space of emotion, consumer identity and community interaction that has long-term durability in the midst of a dynamic market.